New Insights into the Genomic Organization and Splicing of the Doublesex Gene, a Terminal Regulator of Sexual Differentiation in the Silkworm Bombyx mori - Duan, Jianping (Public Library of Science, 2013)

(untitled)
Sex-determination mechanisms differ among organisms. The primary mechanism is diverse, whereas the terminal regulator is relatively-conserved. We analyzed the transcripts of the Bombyx mori doublesex gene (Bmdsx), and reported novel results concerning the genomic organization and expression of Bmdsx. Bmdsx consists of nine exons and eight introns, of which two exons are novel and have not been reported previously. Bmdsx transcripts are spliced to generate seventeen alternatively-spliced forms and eleven putative trans-spliced variants. Thirteen of the alternatively-spliced forms and five of the putative trans-spliced forms are reported here for the first time. Sequence analysis predicts that ten female-specific, six male-specific splice forms and one splice form found in males and females will result in four female-specific, two male-specific Dsx proteins and one Dsx protein common to males and females. The Dsx proteins are expected to be functional and regulate downstream target genes. Some of the predicted Dsx proteins are described here for the first time. Therefore the expression of the dsx gene in B. mori results in a variety of cis- and trans-spliced transcripts and multiple Dsx proteins. These findings show that in B. mori there is a complicated pattern of dsx splicing, and that the regulation of splicing and sex-specific functions of lepidopteran dsx have evolved complexity.